Where Should Morality Go: A Reexamination of the Confucian Rule by Virtue Thought in the Pre-Qin Dynasty and the Chinese Traditional Ideological Dilemma - Li, Yunlong (Religions, 2024)
The thought of rule by virtue in ancient China holds a significant role in Chinese ideological history. Because of the similarity in nature and authority, morality in ancient China played a similar role to religion in Western countries. The Confucian rule by virtue thought in the pre-Qin dynasty profoundly influenced subsequent generations. During the pre-Qin period, Confucian rule by virtue thought evolved—from personal cultivation to statecraft, integrating law and ritual. Concepts of rule by rite, rule by man, and rule by virtue intertwined with the legal philosophies of Confucius, Mencius, and Xunzi. Confucian moral governance focuses on human values and life quality, retaining relevance today. Constrained by historical and social contexts, it had unique dilemma and unobservable limitations. In order to eliminate the ideological dilemma, a return to virtue and law while adhering strictly to their boundaries is a feasible path for the Confucian rule by virtue thought from the pre-Qin Dynasty to the modern era.